Study on Wireless Network and Restrictive Approaches to Enhance the Data Security - Ponkoodalingam, Kannan; Nitashine, Baskaran; Deshinta, Arrova Dewi (INTI International University, 2018)
Many organizations nowadays use wireless networks or Wi-Fi (Wireless Fidelity) networks. This is because of the resilience and flexibility, simplicity in installing, and lower costs when compared to fixing wired cables all over an organization’s infrastructure. The Wi-Fi technology are not only installed on private wireless networks, it is installed speedily on the public wireless network via hotspots. For example, hotels, airports, restaurants and more. Wi-Fi is certain type of WLAN (Wireless Local Area Network) whereby the WLAN technology is the quickest growing technology besides the Internet. In response with the growing of the security hazards on WLAN’s data security and unauthorized corporate is what the network administrators and information security managers must give an extra attention to. Hence, the scope of this research focuses on the wireless network security in terms of threats and restrictive approaches whereby multi-factor authentication technology is proposed as one of the ways to mitigate the threats. Five hypothesis are included to support this study and they are analyzed using quantitative and qualitative software i.e. SPSS and QDA Miner. The result shows that multi-factor authentication should be implemented as additional security feature on the wireless network